2023
DOI: 10.21203/rs.3.rs-3621420/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acquired amphotericin B resistance and fitness trade-off compensation in Candida auris

Hans Carolus,
Dimitrios Sofras,
Giorgio Boccarella
et al.

Abstract: Candida auris is an emergent human fungal pathogen of growing concern due to common drug resistance to all major antifungal drug classes. Although resistance to amphotericin B (AMB) has been detected in 30 to 60% of clinical isolates of C. auris, mechanisms of AMB resistance remain poorly characterized. Here we present a large-scale investigation of how AMB resistance can be acquired through genetic adaptation. We typed 441 in vitro and in vivo evolved C. auris lineages from four AMB-susceptible clinical strai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…It is likely that the residual Erg6 activity observed in the erg6a Δ mutants can rescue the most deleterious consequences of loss of Erg6 function, while still conferring amphotericin B resistance due to cholesta-type sterols production. A comparable scenario was recently reported in C. auris evolved isolates, where erg6 mutations conferring amphotericin B resistance emerged in vivo, occasionally accompanied by other mechanisms that compensate for fitness trade-offs (71). Similarly, the loss of Erg6a function in mucoralean pathogens may arise in vivo and lead to mucormycosis infections that do not respond to first-line antifungal therapies, and may challenge recent and exciting developments in polyene antifungal drug discovery (73).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It is likely that the residual Erg6 activity observed in the erg6a Δ mutants can rescue the most deleterious consequences of loss of Erg6 function, while still conferring amphotericin B resistance due to cholesta-type sterols production. A comparable scenario was recently reported in C. auris evolved isolates, where erg6 mutations conferring amphotericin B resistance emerged in vivo, occasionally accompanied by other mechanisms that compensate for fitness trade-offs (71). Similarly, the loss of Erg6a function in mucoralean pathogens may arise in vivo and lead to mucormycosis infections that do not respond to first-line antifungal therapies, and may challenge recent and exciting developments in polyene antifungal drug discovery (73).…”
Section: Discussionsupporting
confidence: 74%
“…Despite these defects, the absence of Erg6 activity can provide a selective advantage by conferring amphotericin B drug resistance, as seen in multiple Candida species and Cryptococcus neoformans (17– 21, 23). Indeed, a recently conducted large-scale study, involving a collection of over four hundred C. auris strains evolved from clinical isolates, reported that mutations in erg6 were the most frequent cause of amphotericin B resistance (71). Exploring the function of Erg6 in Mucor species presented additional challenges due to the presence of three different Erg6 paralogs.…”
Section: Discussionmentioning
confidence: 99%
“…Strain construction. For strain construction, C. auris cells were prepared as described by Carolus et al 53 . For electroporation, 40 l of competent cells was mixed with the transformation mixture and transferred to 2 mm electroporation cuvettes (Pulsestar, Westburg).…”
Section: Generation Of Mutant Strains Of Genes B9j08_001458 (Scf1) An...mentioning
confidence: 99%
“…Inactivation or modification of ERG3 or ERG6 impacts drug susceptibility of many Candida species [14,20,22,[28][29][30][31][32][33]. For example, loss of Erg6 function reduces susceptibility to nystatin and polyenes in C. glabrata [28,34,35]. Loss of Erg3 function confers resistance to azoles in C. albicans, C. parapsilosis, C. dubliniensis and resistance to polyenes in C. albicans and C. lusitaniae [22,[29][30][31]36,37].…”
Section: Introductionmentioning
confidence: 99%